Development, implementation and preliminary study of a PDA-based bacteriology collection system - Blaya, Joaquin (American Medical Informatics Association, 2006)
Partners In Health (PIH) and its sister organization in Lima, Peru, Socios En Salud (SES), treat a majority of multidrug-resistant tuberculosis (MDR-TB) patients in Peru, in conjunction with the Peruvian National TB Program (NTP). Monthly bacteriology tests, which must be collected from health establishments located across this major city, are an integral part of this treatment. Currently, a SES employee visits each health establishment to collect this information by hand, process it and type it into an electronic medical record system (PIH-EMR). In this paper, we describe the development and implementation of a personal digital assistant (PDA)-based electronic system to collect, verify and upload monthly bacteriology data into the PIH-EMR. After an initial implementation period, we performed a pilot study to test the use of this system. We completed a baseline assessment in two health districts and then implemented the electronic system in one of the districts while the control site continued to use the paper-based system during the same period. The PDA-based system had a processing time of 6.2 days, significantly lower than measurements for both the baseline [54.8] and control sites [64.4] (both p<0.0001). It was also able to reduce the frequency of discrepancy from 10.1% to 2.8% (p<0.0001) and receive positive feedback from the users. Finally, the system’s cost would be recuperated in three months from time savings due to increased work efficiency. This system will be the subject of a larger study to determine its impact on delays, errors and costs.